Frog‐Derived Neuroregenerative‐Peptide‐Reinforced Bioactive Hydrogels with Injectability, Thermosensitivity, and Enhanced Neurotrophic Function for Repairing Central Nervous Injuries - Zhengang Sun; Zhenjuan Sun; Chenxi Du; Hongyu Chen; Xingchao Zhang; Yuanyuan Liu; Fang Dong; Xuexiao Ma; Gang Wei; Haiyuan Yue (Small Structures)
The clinical treatment of central nervous system (CNS) injuries presents significant challenges due to the inflammatory microenvironment (IME) induced by CNS injury, which inhibits spontaneous neuronal regeneration. Biomimetic biomaterial‐based IMEs for CNS repair, which facilitate the reconstruction of neural regeneration circuits, show promise. In this study, the development of novel bioactive peptide nanofibers (PNFs)/chitosan (CS)/VD11 (VDELWPPWLPC) hydrogels (named as PCV) is reported, created by reinforcing composite PNFs/CS with a frog‐derived neuroregenerative peptide (VD11). The created hydrogels exhibit a 3D porous structure, high thermosensitivity, good injectability, and enhanced neurotrophic properties, making them promising candidates for CNS repair. The in vitro tests indicate that PCV hydrogels can promote the proliferation, migration, and differentiation of stem cells into neurons, as well as guide axonal growth. Additionally, they help mitigate inflammatory responses by reducing macrophage activation and astrocyte proliferation, while promoting neovascularization. The in vivo animal experimentsdemonstrate that PCV hydrogels enhance blood supply to the damaged area and promote the migration and colonization of endogenous neural stem cells to support axonal growth. Furthermore, PCV hydrogels reduce immune responses and limit excessive astrocyte proliferation, significantly improving motor function recovery in rats with spinal cord injuries. In these findings, it is suggested that these hydrogels can provide a promising strategy for treating CNS injuries by regulating IME.